2020
DOI: 10.1089/biores.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Pathways, Myelination Disorders, Neurodegenerative Diseases, and Epigenetic Drugs

Abstract: In this review we outline a rationale for identifying neuroprotectants aimed at inducing endogenous Klotho activity and expression, which is epigenetic action, by definition. Such an approach should promote remyelination and/or stimulate myelin repair by acting on mitochondrial function, thereby heralding a life-saving path forward for patients suffering from neuroinflammatory diseases. Disorders of myelin in the nervous system damage the transmission of signals, resulting in loss of vision, motion, sensation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 235 publications
(335 reference statements)
0
8
0
Order By: Relevance
“…The anti‐aging and cognition‐enhancing gene KL can act through its pleiotropic protective functions to counteract the diverse signaling cascades and mechanisms underlying senescence (Moos et al, 2020). Therapeutic approaches increasing KL gene expression can prevent further neurodegeneration and memory loss associated with aging and Alzheimer's disease (AD) (Abraham et al, 2016; Dubal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti‐aging and cognition‐enhancing gene KL can act through its pleiotropic protective functions to counteract the diverse signaling cascades and mechanisms underlying senescence (Moos et al, 2020). Therapeutic approaches increasing KL gene expression can prevent further neurodegeneration and memory loss associated with aging and Alzheimer's disease (AD) (Abraham et al, 2016; Dubal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches increasing KL gene expression can prevent further neurodegeneration and memory loss associated with aging and Alzheimer's disease (AD) (Abraham et al, 2016; Dubal et al, 2015). Although KL is mainly expressed in the kidney and does not cross the blood‐brain barrier (BBB) (Leon et al, 2017), it is also expressed in the brain (Masso et al, 2015; Moos et al, 2020). Our study used intracerebroventricular administration of AAVs as a delivery approach to increase KL expression in the CNS as a promising therapeutic strategy to normalize some relevant aging hallmarks present in SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KL protein is almost 130 kDa with a putative signal sequence at the N-terminus, a single transmembrane domain near the C-terminus and a short cytoplasmic domain (Razzaque et al, 2012). KL is a single-pass trans-membrane protein secreted in the brain, kidney, eye, testis, ovary, pancreas, pituitary and parathyroid gland tissues (Kuro-o, 2010;Moos et al, 2020). The KL protein family has three members: alpha, beta and gamma.…”
Section: Klotho Proteins and Biological Functionsmentioning
confidence: 99%
“…Although recent reports doubt if this endogenous transcript produces a functional protein 4 , different groups have reported that increasing the levels of s-KL or KL1 through recombinant protein administration or gene transfer approaches confers clear beneficial properties [5][6][7][8] . Klotho can modulate several pathways related to aging progression, which include among others, the inhibition of insulin growth factor-1 (IGF-1)/insulin signaling and Wnt pathways, involved in senescence and fibrosis, respectively 9 . It also reduces oxidative stress and exhibits anti-inflammatory effects, reducing cellular damage during aging 10 .…”
mentioning
confidence: 99%